Miotoksisitas Statin: Kajian Stres Oksidatif - Zulfahmidah; Safei, Imran; Fajriansyah (Pengurus Pusat Ikatan Apoteker Indonesia, 2021)
Statins are a family of drugs used to treat hyperlipidemia with a recognized capacity to prevent disease occurrence. Widespread use of statins is limited by the presence of associated toxicity or intolerance, which affects the level of drug monitoring. Statin toxicity or intolerance varies from 10-15%. Statin-associated muscle symptoms are the most common statin toxicity (SAMS). In this review, we aim to report on the mechanism of action of statins causing the muscle symptoms of SAMS. The results showed that statins cause mitochondrial dysfunction due to oxidative stress. The mechanism of oxidative stress due to statins is due to the inhibition of ubiquinone protein, activation of iNOS, decreased mitochondrial biogenesis, reduction of mitochondrial oxidative phosphorylation. the data reported as a whole may suggest that statins have a major effect on mitochondrial function related to oxidative stress